Kudoa spp. (Myxozoa, Multivalvulida) parasitizing fish caught in Aracaju, Sergipe, Brazil - Eiras,Jorge Costa (2016)
Abstract This study reports on Kudoa spp. (Myxozoa, Multivalvulida) from the fish species Lutjanus analis, Bagre marinus, Aspistor luniscutis and Lutjanus jocu, which were caught in Aracaju, state of Sergipe, Brazil. The parasites formed oval plasmodia around the esophagus of L. analis, and elongated plasmodia inside the skeletal muscle of B. marinus, A. luniscutis and L. jocu. Host myoliquefaction was not observed in all the cases studied. The current study provides a morphological and morphometric description of each parasite as well as a comparison with all the species described worldwide. Lack of molecular data impaired specific identification of the parasites. The importance of these parasites is discussed and the need for further studies on infections in Brazilian fish is emphasized because of the high economic impact of some Kudoa species which cause liquefaction in hosts’ muscles and render these fish unsuitable for consumption.